Oil palm shell (OPS) as fine aggregate in concrete properties - Wan Anwar Faiz, Wan Nasaruddin (2012)
This study was conducted to determine the use of oil palm shell (OPS) as fine aggregate in concrete to replace sand in concrete mixture. The main objective of this study is to determine the effectiveness of oil palm shell to produce concrete. Experimental work was conducted in laboratory to determine the characteristic of oil palm shell concrete • by using weight method. In this studies, six different concrete mixes with different the combination of natural material content namely 0%, 5%, 10%, 15%, 20% and 25%. Three sample specimen will be prepared for each concrete mixes. The laboratory tests conducted including sieve analysis, slump test, vebe test, compacting factor test and compressive strength test. The results show that the oil palm shell concrete has strong compressive strength. Using the oil palm shell as aggregate in concrete can reduce the material cost in construction because of the low cost and abundant agricultural waste. In this experiment, there are several things that can be expected when finish. The following are some of the expected result for this experiment is to get higher compressive strength in lower density of concrete and to achieve the specified strength of OPS concrete that same to the control concrete at 28days.